Sustained Wolbachia-mediated blocking of dengue virus isolates following serial passage in Aedes aegypti cell culture. Issue 1 (8th June 2019) - Koh, Cassandra; Audsley, Michelle D; Di Giallonardo, Francesca; Kerton, Emily J; Young, Paul R; Holmes, Edward C; McGraw, Elizabeth A
Abstract: Wolbachia is an intracellular endosymbiont of insects that inhibits the replication of a range of pathogens in its arthropod hosts. The release of Wolbachia into wild populations of mosquitoes is an innovative biocontrol effort to suppress the transmission of arthropod-borne viruses (arboviruses) to humans, most notably dengue virus. The success of the Wolbachia -based approach hinges upon the stable persistence of the 'pathogen blocking' effect, whose mechanistic basis is poorly understood. Evidence suggests that Wolbachia may affect viral replication via a combination of competition for host resources and activation of host immunity. The evolution of resistance against Wolbachia and pathogen blocking in the mosquito or the virus could reduce the public health impact of the symbiont releases. Here, we investigate if dengue 3 virus (DENV-3) is capable of accumulating adaptive mutations that improve its replicative capacity during serial passage in Wolbachia w Mel-infected cells. During the passaging regime, viral isolates in Wolbachia -infected cells exhibited greater variation in viral loads compared to controls. The viral loads of these isolates declined rapidly during passaging due to the blocking effects of Wolbachia carriage, with several being lost all together and the remainder recovering to low but stable levels. We attempted to sequence the genomes of the surviving passaged isolates but, given their low abundance, were unable to obtain sufficient depth of coverage for evolutionary analysis. In contrast, viral loads in Wolbachia -free control cells were consistently high during passaging. The surviving isolates passaged in the presence of Wolbachia exhibited a reduced ability to replicate even in Wolbachia -free cells. These experiments demonstrate the challenge for dengue in evolving resistance to Wolbachia -mediated blocking.